Dysplasia of Granulocytes in a Patient with HPV Disease, Recurrent Infections, and B Lymphopenia: A Novel Variant of WHIM Syndrome? - Moscato, Giusella M. F.; Giacobbi, Erica; Anemona, Lucia; Di Cesare, Silvia; Di Matteo, Gigliola; Andreoni, Massimo; Mauriello, Alessandro; Moschese, Viviana (Frontiers in Pediatrics, 2017)
WHIM syndrome is a condition for which affected persons have chronic peripheral neutropenia, lymphopenia, abnormal susceptibility to human papilloma virus infection and myelokathexis. Myelokathexis refers to the retention of mature neutrophils in the bone marrow which accounts for degenerative changes and hypersegmentation. Most patients present heterozygous autosomal dominant mutations of the gene encoding CXCR4. Consequently, aberrant CXCL12/CXCR4 signalling impairs the receptor down-regulation causing hyperactivation (gain of function) that affects bone marrow homing for myelopoiesis and lymphopoiesis and the release of neutrophils in the bloodstream. We report the case of a 26-yr-old female with severe foot and hand cutaneous warts since childhood, recalcitrant genital condylomatas, bacterial infections, and intraepithelial cervical neoplasia. Laboratory tests revealed severe B lymphopenia and HPV high and low risk types. HIV testing was negative. Not only CXCR4, but also GATA2, NEMO and CD40L gene mutations were excluded. BM smears revealed, in the presence of a normal cellularity, hyperplasia of myeloid cells (MPO positive) and karyorrhexis, especially in neutrophils and eosinophils. Of note, neutrophils with altered lobation of nuclei connected by long thin chromatin filaments were observed. Our patient presented a clinical and histological picture reminiscent of WHIM in the presence of normal peripheral neutrophil counts and wild-type CXCR4 gene. Although the BM did not reveal a classical pattern of myelokathexis, the observation of consistent signs of neutrophil dysplasia has fuelled the hypothesis of a novel WHIM variant or a novel immunodeficiency. We speculate that abnormalities that affect CXCR4/CXCL12 pair, including GRK levels or activity, might be responsible for this WHIM-like disorder.